2015
DOI: 10.1044/2014_ajslp-13-0153
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Memory in Processing Relative Clauses in Children With Specific Language Impairment

Abstract: Purpose This study investigated the relationship between 2 components of memory—phonological short-term memory (pSTM) and working memory (WM)—and the control of relative clause constructions in children with specific language impairment (SLI). Method Children with SLI and 2 control groups—an age-matched and a younger group of children with typical development—repeated sentences, including relative clauses, representing 5 syntactic roles and 2 levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 47 publications
4
36
0
2
Order By: Relevance
“…However, deficits in cognitive processing may help explain why the children's tense and negation errors increased as the number of functional categories increased within the sentences. Consonant with this latter finding, past work has shown that children's sentence recall scores have been correlated to measures of short-term memory (forward digit recall: Frizelle & Fletcher, 2015;Riches, Loucas, Baird, Charman, & Simonoff, 2010), working memory involving verbal and nonverbal, auditory materials (competing language processing: Poll et al, 2013;listening span: Frizelle & Fletcher, 2015;Riches, 2012;nonverbal, auditory recall: Ebert, 2014), phonological shortterm memory (nonword repetition: Ebert, 2014;Riches, 2012), and speed of processing (Poll et al, 2013). Thus, sentence recall may be diagnostically useful for identifying children with SLI because it is sensitive to children's deficits in both language and cognitive processing.…”
Section: Discussionmentioning
confidence: 84%
“…However, deficits in cognitive processing may help explain why the children's tense and negation errors increased as the number of functional categories increased within the sentences. Consonant with this latter finding, past work has shown that children's sentence recall scores have been correlated to measures of short-term memory (forward digit recall: Frizelle & Fletcher, 2015;Riches, Loucas, Baird, Charman, & Simonoff, 2010), working memory involving verbal and nonverbal, auditory materials (competing language processing: Poll et al, 2013;listening span: Frizelle & Fletcher, 2015;Riches, 2012;nonverbal, auditory recall: Ebert, 2014), phonological shortterm memory (nonword repetition: Ebert, 2014;Riches, 2012), and speed of processing (Poll et al, 2013). Thus, sentence recall may be diagnostically useful for identifying children with SLI because it is sensitive to children's deficits in both language and cognitive processing.…”
Section: Discussionmentioning
confidence: 84%
“…Finally, listening span tasks require children to make true/false judgments of sentences they hear while simultaneously retaining the final word of each for later recall. Across various versions of this task, children with SLI, aged 4 to 14 years, generally do not differ from controls in their ability to judge the truth value of the sentences; however, in terms of words recalled, children with SLI score lower than age- but not language-matched controls (Briscoe & Rankin, 2009; Ellis Weismer, Evans, & Hesketh, 1999; Ellis Weismer et al, 2005; Frizelle & Fletcher, 2015; Laing & Kamhi, 2003; Lum et al, 2012; Mainela-Arnold & Evans, 2005; Mainela-Arnold et al, 2010; Marton & Eichorn, 2014; Marton, Kelmenson, & Pinkhasova, 2007; Marton & Schwartz, 2003; Marton, Schwartz, Farkas, & Katsnelson, 2006; Montgomery & Evans, 2009; Rodekohr & Haynes, 2001; Vugs et al, 2014). In addition to their listening span scores, children with SLI and their age-matched controls differ in the type and amount of nonlist words produced, with children with SLI more likely to give words that had occurred on previous lists, or had occurred elsewhere in the sentence (Ellis Weismer et al, 1999; Marton & Eichorn, 2014; Marton & Schwartz, 2003; Marton et al, 2006, 2007).…”
Section: Working Memory Deficits In Children With Slimentioning
confidence: 99%
“…Deficits with movement operations such as those involved in passives are also reported to result in similar difficulties in passives for children with SLI (van der Lely 1996) and have been hypothesized to be related to deficits in working memory (Montgomery & Evans 2009;Marinis & Saddy 2013), as reported for other constructions involving longdistance dependencies such as relative clauses (Frizelle & Fletcher 2014). Indeed mastery of complex grammatical constructions such as passives requires storing and manipulating verbal sequences in a fashion reminiscent of the working memory system (Baddeley & Jarrold 2007), due to syntactic movement to a noncanonical position.…”
mentioning
confidence: 99%